The moral advantage : how to succeed in business by doing the right thing - Damon, William, 1944- (San Francisco, CA : Berrett-Koehler, 2004)
"Based on interviews with 48 executives in a variety of industries, The Moral Advantage describes the many distinct ways that morality contributes to business success. Some of these ways are familiar (following ethical codes, for example), while others, such as unleashing the powers of moral imagination, have received little or no attention." "Damon details the many ways these business leaders applied their moral sense to strengthen their businesses. For some, it was a matter of directly extrapolating a new business concept from a moral (and often spiritual) worldview. For others, it was a sensitivity to what consumers needed and a determination to respond effectively to that. For yet others, it was a commitment to a caring and ethical manner of doing business that required inventive approaches to organizing employees. But in every case, Damon shows that it was by adhering firmly to a personal moral code that these men and women ultimately triumphed."--BOOK JACKET.
Introduction: Purpose and success in business -- The moral advantage -- Generative morality: Acts of creation -- Empathic morality and the Golden Rule -- Business ethics that come naturally -- Philanthropy in business: Doing it right -- Forging a moral identity in business.
Includes bibliographical references and index.
Keywords: Business ethics; Success in business -- Moral and ethical aspects; Social responsibility of business; Industrial management -- Moral and ethical aspects; Organizational behavior -- Moral and ethical aspects; Businesspeople -- Interviews; Successful people -- Interviews; Businesspeople -- Interviews; Successful people